2017
DOI: 10.1002/pd.5160
|View full text |Cite
|
Sign up to set email alerts
|

Risk for chromosomal aberrations in apparently isolated intrauterine growth restriction: A systematic review

Abstract: Due to a limited number of cases and insufficient quality of evidence, high-quality well standardized case-controlled trials should be conducted, further exploring the risk for chromosomal aberrations in pregnancies with isolated IUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…While gestalt plays an important role in both fetal and pediatric dysmorphology, an emphasis on a systematic approach and not rapid diagnosis should be emphasized . Ultrasound documentation protocols by body system and inclusive of amniotic fluid and fetal weight are encouraged . A second analysis focused on subtle, minor findings also should be systematic, referencing normal fetal measurements as needed (Table ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While gestalt plays an important role in both fetal and pediatric dysmorphology, an emphasis on a systematic approach and not rapid diagnosis should be emphasized . Ultrasound documentation protocols by body system and inclusive of amniotic fluid and fetal weight are encouraged . A second analysis focused on subtle, minor findings also should be systematic, referencing normal fetal measurements as needed (Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…16 Ultrasound documentation protocols by body system and inclusive of amniotic fluid and fetal weight are encouraged. [17][18][19] A second analysis focused on subtle, minor findings also should be systematic, referencing normal fetal measurements as needed (Table 1). [21][22][23][24][25] Minor features entered verbatim can now be retrieved by artificial intelligence software searches of electronic medical records.…”
Section: Casementioning
confidence: 99%
“…[31][32][33] Chromosomal abnormalities have been suggested to contribute to up to 5% of FGR cases; triploidy and trisomy 13 and 18 are important considerations in early-onset FGR and the risk of many aneuploidies is higher in the presence of structural fetal anomalies. [34][35][36] In 1%-6% of cases of FGR with normal karyotype, submicroscopic (micro) duplications/deletions can be found using chromosomal microarray analysis, 35 even when FGR is an apparently isolated finding. 37 FGR is also more prevalent in fetuses with structural malformations, and the risk increases when multiple anomalies are present.…”
Section: Etiology Of Fetal Growth Restrictionmentioning
confidence: 99%
“…Chromosomal anomalies were reported to account for up to 19% of fetuses with FGR , with triploidies being the most common anomaly in fetuses below 26 weeks, and trisomy 18 above 26 weeks (Table ). In apparently isolated FGR fetuses at any gestational age (10 to 39 weeks), a recent systematic review by Sagi‐Dain et al (2017) including 14 studies, found a 6.4% (47/874) chromosomal abnormality rate. Nevertheless, all the included studies were retrospective and the quality of evidence of these selected manuscripts was defined as low in all except one study.…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%